Redesigning China's superblock neighbourhoods: policies, opportunities and challenges. Issue 6 (2nd November 2017) - Kan, Har Ye; Forsyth, Ann; Rowe, Peter
ABSTRACT: In February 2016, China's State Council released a set of guidelines representing a change in the country's approach toward neighbourhood design: to move away from superblock neighbourhoods and create a finer network of urban blocks and streets. The paper traces the circumstances that prompted this change, drawing on a comparative review of international literature and practice, and explores the opportunities and challenges for urban design. While modifications of the superblock are somewhat overdue, this current mode of organization should not be entirely abandoned. The suggestions and overall blueprint warrant a more circumspect approach and should be adopted with discretion.